Classroom Participation and democratic competency : a study case - Delbury, Perrine (2020)
The aim of this article is to understand how day-to-day student classroom participation in an ordinary secondary Chilean school contributes to civic education towards democratic competency. The qualitative method adopted an ethnomethological perspective and used participant observation, unstructured interviews and document review techniques, all later analyzed inductively. The results show a lack of definition of classroom participation in institutional documents, sporadic implementation of participating events and a consensual passive role of students in the classroom. It concludes that classroom participation tends to teach students to consider their interactions as interruptions when dealing with their life outside the classroom and illegitimate in their expression, contributing negatively to their development of democratic competency.